Relative contribution of decreased productivity and survival to recent changes in the demographic trend of the Rivière George Caribou Herd - Crête, M.; Couturier, S.; Hearn, B.J.; Chubbs, T.E. (Rangifer, 1996)
The Rivière George caribou herd (RGCH) was numerically low during the middle part of the century but apparently erupted in the sixties and the seventies. Puberty was early and pregnancy rate was high among RGCH females from 1973 until the mid-eighties when fecundity decreased significantly, in particular among sub-adults; productivity remained low in 1992. Autumn calf:female ratios reflected this trend in pregnancy, exceeding 50 calves: 100 cows between 1973 and 1983, but dropping thereafter progressively to a low of 24 in 1992. In 1993, this ratio rebounded back to 42. Annual adult survival rate of radio-collared females was high (0.95) at the beginning of the monitoring in 1984, but exhibited a variable but declining trend until 1992. Simulations were conducted to estimate the demographic trend of the RGCH between 1984 and 1992, using annual survival rates of radio-collared animals and annual autumn calffemale ratios to estimate calf production. Age structure played a minor role in estimating the finite rate of increase (Lamda). According to the simulations, the RGCH increased in size until 1987, and showed a slight decrease thereafter. The herd should have decreased by 12-15% between 1988 and 1993, according to the simulations. Productivity first caused a decline in Lamda, but in recent years decreased survival contributed slightly more than productivity to the reduction in Lamda. Estimation of the herd size by means of aerial censuses in 1976, 1984, 1988 and 1993 suggested a similar pattern in demographic trend, differences being statistically meaningless. We speculated on the future of the RGCH, that could have erupted after many decades of unfavourable weather. The herd will exhibit a rapid descent to low numbers if wolves show a numerical response to current caribou abundance, or if lichen availability on the winter range decreases due to competition with the adjacent and increasing Rivière aux Feuilles herd; otherwise it will exhibit dampened oscillations, whose amplitude will depend on the time-lag of vegetation reaction to decrease grazing pressure on the summer range.